The Insurgent Barricade - Traugott, Mark (Book collections on Project MUSE., 2010)
"To the barricades!" The cry conjures images of angry citizens, turmoil in the streets, and skirmishes fought behind hastily improvised cover. This definitive history of the barricade charts the origins, development, and diffusion of a uniquely European revolutionary tradition. Mark Traugott traces the barricade from its beginnings in the sixteenth century, to its refinement in the insurrectionary struggles of the long nineteenth century, on through its emergence as an icon of an international culture of revolution. Exploring the most compelling moments of its history, Traugott finds that the.